Social Simulation in the Social Sciences: A Brief Overview. (June 2014) - Squazzoni, Flaminio; Jager, Wander; Edmonds, Bruce
This article provides an overview of the social simulation approach to the study of social phenomena. We focus especially on the relevance of heterogeneity of social behavior and dynamics and the complex interplay of agent behavior and social structure. The article identifies the peculiarities and the explanatory achievements of this approach and then discusses its prospects and challenges. Special attention is given to (i) how micro-level behavioral detail can be used to understand social patterns and dynamics; (ii) the importance of the meso level of social networks; and (iii) the two-way, process linkages between micro and macro aspects as a fundamental source of social uncertainty and unpredictability.